2017
DOI: 10.1097/ccm.0000000000002055
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Usage and Outcomes Between Nurse Practitioner and Resident-Staffed Medical ICUs

Abstract: We found no difference in mortality between an nurse practitioner-staffed medical ICU and a resident-staffed physician medical ICU. Our study adds further evidence that advanced practice providers can render safe and effective ICU care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
(18 reference statements)
2
21
0
2
Order By: Relevance
“…This review included 15 studies with 23 681 participants across five countries including Australia [ 28 30 ], Canada [ 31 , 32 ], New Zealand [ 33 ], UK [ 34 ], and USA [ 35 41 ], where the nomenclature for nurses in advanced practice was “NP.” A total of 14 studies [ 28 41 ] were published while one was an unpublished manuscript (Roche T, Gardner GE, Jack L: The effectiveness of emergency nurse practitioner service in the management of patients presenting to rural hospitals with chest pain: a multisite prospective longitudinal nested cohort study. In preparation.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This review included 15 studies with 23 681 participants across five countries including Australia [ 28 30 ], Canada [ 31 , 32 ], New Zealand [ 33 ], UK [ 34 ], and USA [ 35 41 ], where the nomenclature for nurses in advanced practice was “NP.” A total of 14 studies [ 28 41 ] were published while one was an unpublished manuscript (Roche T, Gardner GE, Jack L: The effectiveness of emergency nurse practitioner service in the management of patients presenting to rural hospitals with chest pain: a multisite prospective longitudinal nested cohort study. In preparation.)…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were conducted between 2006 and 2016. As regards the setting, six studies [ 28 30 , 32 , 33 ] focused on the EDs, six [ 31 , 34 , 35 , 37 , 38 , 41 ] on the ICU, two [ 36 , 40 ] on the trauma centers, and one on the stroke center [ 39 ]. The sample sizes ranged from 103 [ 31 ] to 9066 [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the workflow is similar and Scherzer et al found no significant difference in patient mortality between the two MICUs at our institution. 19 Despite these limitations, the study provided unique insight into caregivers' perspectives on specific team behaviors, which is necessary to inform quality improvement initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Scope-of-practice laws for NPs are a contentious policy issue in the US, with some states allowing independent practice for NPs without physician oversight and others requiring physician oversight for all APRN practice [26]. There is substantial evidence that increasing NP scope of practice is not only safe and effective, but also increases access to care for underserved populations [27][28][29]. For RNs, the key law affecting their practice is the Nurse Licensure Compact.…”
Section: Introductionmentioning
confidence: 99%